Hutchison Medallist 1. Wave-Dominated to Tide-Dominated Coastal Systems: A Unifying Model for Tidal Shorefaces and Refinement of the Coastal- Environments Classification Scheme - Dashtgard, Shahin E.; Vaucher, Romain; Yang, Byongcheon; Dalrymple, Robert W. (Geoscience Canada, 2021)
Coastal depositional systems are normally classified based on the relative input of wave, tide, and river processes. While wave- through to river-dominated environments are well characterized, environments along the wave-to-tide continuum are relatively poorly understood and this limits the reliability and utility of coastal classification schemes. Two tidal shoreface models, open-coast tidal flats (OCTF) and tidally modulated shorefaces (TMS), have been introduced for mixed wave-tide coastal settings. Following nearly two decades of research on tidal shorefaces, a number of significant insights have been derived, and these data are used here to develop a unified model for such systems. First, OCTFs are components of larger depositional environments, and in multiple published examples, OCTFs overlie offshore to lower shoreface successions that are similar to TMS. Consequently, we combine OCTFs and TMSs into a single tidal shoreface model where TMS (as originally described) and TMS-OCTF successions are considered as variants along the wave-tide continuum. Second, tidal shoreface successions are preferentially preserved in low- to moderate-wave energy environments and in progradational to aggradational systems. It is probably difficult to distinguish tidal shorefaces from their storm-dominated counterparts. Third, tidal shorefaces, including both TMSs and OCTFs, should exhibit tidally modulated storm deposits, reflecting variation in storm-wave energy at the sea floor resulting from the rising and falling tide. They may also exhibit interbedding of tidally generated structures (e.g. double mud drapes or bidirectional current ripples), deposited under fairweather conditions, and storm deposits (e.g. hummocky cross-stratification) through the lower shoreface and possibly into the upper shoreface.The development of the tidal shoreface model sheds light on the limitations of the presently accepted wave-tide-river classification scheme of coastal environments and a revised scheme is presented. In particular, tidal flats are components of larger depositional systems and can be identified in the rock record only in settings where intertidal and supratidal deposits are preserved; consequently, they should not represent the tide-dominated end-member of coastal systems. Instead, we suggest that tide-dominated embayments should occupy this apex. Tide-dominated embayments exhibit limited wave and river influence and include a wide range of geomorphological features typically associated with tidal processes, including tidal channels, bars and flats.